Feasibility and Effectiveness of Distributing Micronutrient Sprinkles to Reduce Prevalence of Anemia - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The study on dairy value chains that will be conducted in Northern Senegal tests whether a health-related product (micro-fortified yogurt) targeted to children can be provided through the logistics of an existing value chain, and whether in return this can be leveraged to enhance the reliability of producers supply within this value chain. This study is conducted with a local milk factory, a recently established social enterprise, striving to produce dairy products with the milk collected from several hundred semi-nomadic small-scale producers in northern Senegal. This study tests: (i) whether the logistic created to collect milk in a remote area can be leveraged to deliver fortified yogurts to infants within its suppliers households; (ii) whether such products effectively help improve the nutritional status (anemia) of these children; and (iii) whether these health services encourage suppliers (and in particular women) to increase their milk delivery to the milk factory.